Sociodemographic Profile, Perceived Stress, and Coping Strategies Among ICU Nurses: A Cross-Sectional Study from Western India - Meena, Roshan; Acharya, Rajendra Kumar; Seervi, Ashok; Gehlot, Sanjay (Psychocentrum Review, 2025)
Intensive Care Unit (ICU) nursing is one of the most demanding healthcare specialities, with nurses facing significant occupational stress. In India, critical nursing shortages and resource constraints further compound these challenges. Understanding the relationship between sociodemographic factors, perceived stress, and coping strategies is essential for developing targeted interventions. This cross-sectional study examined sociodemographic profile, perceived stress levels, and coping strategies among 184 ICU nurses at a tertiary care hospital in Western India. Data were collected using a sociodemographic questionnaire, Perceived Stress Scale (PSS-10), and COPE Inventory. Results revealed 70.7% of participants experienced moderate to high perceived stress (48.4% moderate, 22.3% high). Significant associations were found between stress levels and younger age (p<0.001), unmarried status (p<0.001), higher educational qualifications (p=0.004), limited ICU experience (p<0.001), nuclear family structure (p<0.001), and absence of children (p<0.001). Gender, service area, and duty shift showed no significant associations. Nurses predominantly employed adaptive coping strategies, including positive reinterpretation (73.4%), acceptance (66.3%), instrumental social support (65.2%), and active coping (62.5%). Maladaptive strategies were less frequent, with behavioral disengagement at 27.7% and substance use at 13.6%. Religious coping was utilized by 15.8%, reflecting cultural influences. Findings highlight a substantial psychological burden among ICU nurses and identify vulnerable subgroups requiring targeted interventions. The predominant use of adaptive coping suggests existing resilience that can be strengthened through comprehensive support programs, mentorship for younger nurses, and culturally appropriate stress management interventions.